Administration of Tetrahydrobiopterin (BH4) Protects the Renal Microcirculation From Ischemia and Reperfusion Injury. (October 2017) - Rahmania, Lokmane; Orbegozo, Diego; Su, Fuhong; Taccone, Fabio Silvio; Vincent, Jean-Louis; De Backer, Daniel
Abstract : BACKGROUND: Abdominal aortic aneurysm surgery with suprarenal cross-clamping is often associated with renal injury. Although the mechanism underlying such injury is unclear, tissue ischemia and reperfusion, which induces endothelial dysfunction and decreases the availability of tetrahydrobiopterin (BH4), may play a role. We evaluated whether BH4 administration prevents renal ischemia/reperfusion injury in an animal model of aortic cross-clamping. METHODS: Nineteen anesthetized, mechanically ventilated, and invasively monitored adult sheep were randomized into 3 groups: sham animals (n = 5) that underwent surgical preparation but no aortic clamping; an ischemia/reperfusion group (n = 7), where the aorta was clamped above the renal arteries for 1 hour, and a BH4 group (n = 7), in which animals received 20 mg/kg of BH4 followed by aortic cross-clamp for 1 hour. Animals were followed for a maximum of 6 hours after reperfusion. The renal microcirculation was evaluated at baseline (before clamping), and 1, 4, and 6 hours after reperfusion using side-stream dark field videomicroscopy. The renal lactate-to-pyruvate ratio was evaluated using microdialysis. The primary outcome was the change in proportion of small perfused vessels before and after injury. Secondary outcomes were renal tissue redox state and renal function. RESULTS: Ischemia/reperfusion injury was associated with increases in heart rate and mean arterial pressure, which were blunted by BH4 administration. From the first to the sixth hour after reperfusion, the small vessel density (estimated mean difference [EMD], 1.03; 95% confidence interval [CI], 0.41–1.64; P = .003), perfused small vessel density (EMD, 0.84; 95% CI, 0.29–1.39; P = .005), and proportion of perfused small vessels (EMD, 8.60; 95% CI, 0.85–16.30; P = .031) were altered less in the BH4 than in the ischemia/reperfusion group. The renal lactate-to-pyruvate ratios were lower in the cortex in the BH4 than in the ischemia/reperfusion group from the first to the sixth hour after reperfusion (EMD, −19.16; 95% CI, −11.06 to 33.16; P = .002) and in the medulla from the first to the fourth hour (EMD, −26.62; 95% CI, −18.32 to 38.30; P = .020; and EMD, −8.68; 95% CI, −5.96 to 12.65; P = .019). At the sixth hour, serum creatinine was lower in the BH4 than in the ischemia/reperfusion group (EMD, −3.36; 95% CI, −0.29 to 1.39; P = .026). CONCLUSIONS: In this sheep model of renal ischemia/reperfusion, BH4 pretreatment reduced renal microvascular injury and improved renal metabolism and function. Further work is needed to clarify the potential role of BH4 in ischemia/reperfusion injury. Abstract : Supplemental Digital Content is available in the text.Published ahead of print June 17, 2017.